Multidimensional Structure Of Maternal Sleep Quality In The Third Trimester: Psychometric Evaluation - Nurul Jannah; Gunavathy Selvarajh (PT Inovasi Pratama Internasional, 2026)
Beground : Sleep disturbances are highly prevalent during late pregnancy and have been associated with maternal mental health vulnerability and adverse perinatal outcomes. Emerging evidence suggests that sleep quality in the third trimester is context-specific and may not represent a single, uniform construct. However, the latent structure of maternal sleep quality in late pregnancy has not been sufficiently examined using a theory-driven psychometric approach. Methods : A community-based cross-sectional study was conducted among women in the third trimester of pregnancy (≥28 weeks). The Maternal Sleep Quality Index for the Third Trimester – Indonesian Version (MSQI-T3-ID), a newly developed eight-item self-report instrument, was administered. The hypothesized three-dimensional structure—Sleep Initiation and Continuity, Pregnancy-Specific Disturbance, and Daytime Impact and Fatigue—was evaluated using Confirmatory Factor Analysis within a Structural Equation Modeling framework. Results : Confirmatory factor analysis supported a multidimensional model of maternal sleep quality in late pregnancy. The model demonstrated acceptable fit indices (CFI = 0.95; TLI = 0.93; RMSEA = 0.094; SRMR = 0.027). All items loaded significantly on their respective latent dimensions, with standardized factor loadings ranging from 0.91 to 0.99 (p < .001), indicating a coherent internal structure. Conclusion : The findings provide empirical support for conceptualizing sleep quality in late pregnancy as a multidimensional construct. This study provides initial structural validity evidence for a brief, trimester-specific sleep quality instrument. Keywords : Maternal sleep quality; Third trimester pregnancy; Psychometric validation.